2016
DOI: 10.1152/jn.01082.2015
|View full text |Cite
|
Sign up to set email alerts
|

Repetition priming-induced changes in sensorimotor transmission

Abstract: When a behavior is repeated performance often improves, i.e., repetition priming occurs. Although repetition priming is ubiquitous, mediating mechanisms are poorly understood. We address this issue in the feeding network ofAplysia Similar to the priming observed elsewhere, priming inAplysiais stimulus specific, i.e., it can be either "ingestive" or "egestive." Previous studies demonstrated that priming alters motor and premotor activity. Here we sought to determine whether sensorimotor transmission is also mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…This suggests a major contribution from a dihydropyridine (DHP)sensitive calcium current. Consistent with this idea, a current of this nature has been characterized in B21 with the use of voltage-clamp techniques (Svensson et al 2016). To determine whether this current makes a major contribution to the spikeinduced increase in calcium fluorescence, we performed experiments in which we alternated between the injection of brief current pulses to trigger spiking in B21 and current injections that produced a subthreshold depolarization of~20 mV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a major contribution from a dihydropyridine (DHP)sensitive calcium current. Consistent with this idea, a current of this nature has been characterized in B21 with the use of voltage-clamp techniques (Svensson et al 2016). To determine whether this current makes a major contribution to the spikeinduced increase in calcium fluorescence, we performed experiments in which we alternated between the injection of brief current pulses to trigger spiking in B21 and current injections that produced a subthreshold depolarization of~20 mV.…”
Section: Resultsmentioning
confidence: 99%
“…For example, neuropeptides play an important role in determining whether motor programs are ingestive or egestive. A previous study demonstrated that the nifedipine-sensitive current in B21 is modulated by peptides (Svensson et al 2016). It is increased by a peptide released during the priming of ingestive activity and decreased by a peptide released during the priming of egestive activity.…”
Section: Discussionmentioning
confidence: 95%
“…To determine whether this is the case we compared the STE observed under control conditions (normal ASW) to the STE observed in the presence of nifedipine. Nifedipine blocks a calcium current induced in B21 at relatively low voltages 31 and either reduces or eliminates increases in background calcium resulting from subthreshold changes in membrane potential 13 . We found that in the presence of nifedipine the facilitation that we observed was greatly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has, for instance, been observed that, as a behavior is repeated, certain motor--related neural activities become more probable under certain conditions (e.g., Costa 2007;Wickens et al 2007;Graybiel 2008;Verstynen & Sabes 2011;Hikosaka et al 2013;Kim et al 2015;Anderson 2016). together are subsequently more likely to be active together under certain conditions, and vice versa (e.g., Hebb 1949;Klaes et al 2012). These changes can happen rapidly (within milliseconds), and involve intracellular biochemical changes which influence synaptic transmission among other things (e.g., Friedman et al 2015;Cichon and Gan 2015;Svensson et al 2016). They can also involve rapid morphological changes (within minutes to hours) to neurons and their synaptic connections (e.g., Kandel 2001;Dash et al 2004;Fu et al 2012;Bailey et al 2015;Chen et al 2015;Hayashi--Takagi et al 2015).…”
Section: The Wild Coincidence Objection: An Empirical Objection Withomentioning
confidence: 99%